Self-Assembled Ordered Nanostructure of Zwitterionic Co-Solutes Induces Localized High-Concentration Electrolytes for Ultrastable and Efficient Zinc Metal Anodes - Huang, Shengyang; Hu, Zuyang; Mo, Xin Wang; Park, Yeonju; Kim, Jun Su; Jang, Gun; Min, Dong Hyun; Fu, Hao; Xiong, Peixun; Wen, Zhipeng; Jung, Young Mee; Kim, Jaeyun; et al. (Nano-Micro Letters, 2026)
Localized high-concentration electrolytes (LHCEs) are considered as promising electrolyte candidates to resolve technical issues of metal batteries owing to their unique interfacial properties and solvation structures. Herein, we propose a self-assembly chemical strategy into the LCHEs induced by ordered nanostructure of zwitterionic co-solutes for highly efficient and ultrastable zinc (Zn) metal batteries. Through the systematic screening of six zwitterionic compounds, 3-(decyldimethylammonio)propanesulfonate salt (C10) with the decyl chain and zwitterions was determined as an optimum to construct quasi-spherical aggregates with a periodic length of 3.77 nm, as confirmed by comprehensive synchronous small-angle X-ray scattering, Guinier, pair distance distribution function, Porod, and other spectroscopic characterizations and molecular dynamic simulation. In particularly, this self-assembled structure in electrolyte environments was attributed to increasing the proportion of both contact and aggregated ion pairs for the formation of LHCEs as well as to providing fast and selective Zn2+ conducting channels and uniform solid electrolyte interfaces for facilitated charge transfer kinetics. Moreover, the preferential adsorption of the self-assembled C10 on the Zn(002) surface modulated the electrical double layer to suppress hydrogen evolution and corrosion reactions. Consequently, the Zn||Zn symmetric cells in Zn(OTf)2/C10 electrolytes showed long-term plating/stripping behaviors over 2800 h at 1 mA cm−2 and 1 mAh cm−2 as well as over 1200 h even at 5 mA cm−2 and 5 mAh cm−2 with a very high depth of discharge of 42.7%. Furthermore, the Zn||VO2/CNT full cells in Zn(OTf)2/C10 electrolytes delivered a record-high capacity of 8.10 mAh cm−2 at an ultrahigh cathode mass loading of 50 mg cm−2 after 150 cycles. Highlights: 1 Self-assembled zwitterion (C10) induces localized high-concentration electrolytes, regulating Zn2+ solvation, guiding selective ion transport, and enabling uniform solid electrolyte interface formation. 2 A comprehensive set of advanced analyses (Guinier, PDDF, Porod) combined with spectroscopy and simulations reveals that C10 self-assembles into 3.8 nm quasi-spherical aggregates and bilayer-like interfacial structures. 3 C10 enables ultrastable cycling (>2800 h) in symmetric cells and record areal capacity (8.1 mAh cm−2 at 50 mg cm−2) in Zn||VO2/CNT full cells, highlighting its practical potential for high-energy Zn batteries.